Intertheory Relations in Cognitive Science: Privileged Levels and Reductive Strategies - Jesús Ezquerro; Fernando Martínez Manrique (Crítica)
Research in cognitive science has often assumed the existence of a privileged level that unifies theoretical explanations arising from different disciplines. Philosophical accounts differ about the locus of those intertheory relations. In this paper, four different views are analyzed: classical, connectionist, pragmatist, and reductionist, as exemplified in the works of von Eckardt, Horgan and Tienson, Hardcastle, and Bickle, respectively. Their divergences are characterized in terms of the possibility of such a privileged level. The classical view favors a privileged computational level. The connectionist revision tries to draw biological intuitions into computational models to provide a link between neuronsand computations. The pragmatist approach rejects the idea of a privileged level and offers a more eclectic view of cognitive theory building. The reductionist account pursues theoretical unification by means of the reduction of higher level theories to basic level (biological) ones.